From Deception to Redemption: Analyzing Volkswagen’s Reputational Journey Post-Dieselgate - Riswandi, Risky (Open Access Indonesia Journal of Social Sciences, 2024)
The Volkswagen emissions scandal, or "Dieselgate," inflicted a severe blow to the company's reputation and financial standing. This research paper explores Volkswagen's journey from deception to redemption, analyzing its strategies to rebuild trust and restore its brand image. The study employs a mixed-method approach, incorporating qualitative analysis of media coverage and corporate communications alongside a quantitative assessment of stock prices and consumer sentiment data. Findings reveal a complex reputational trajectory, starting with initial denial, progressing to a reluctant acceptance of responsibility, and culminating in proactive measures to regain stakeholder confidence. While Volkswagen has made notable strides in its recovery, the lingering impact of the scandal underscores the formidable challenge of repairing a tarnished reputation. In conclusion, this research provides valuable insights into crisis management, corporate social responsibility, and the dynamics of reputational recovery in the digital age, highlighting the importance of swift action, transparency, and a genuine commitment to change.